Randomized controlled trial of financial incentives during weight‐loss induction and maintenance in online group weight control. Issue 1 (21st December 2021) - West, Delia S.; Krukowski, Rebecca A.; Monroe, Courtney M.; Stansbury, Melissa L.; Carpenter, Chelsea A.; Finkelstein, Eric A.; Naud, Shelly; Ogden, Doris; Harvey, Jean R.
Abstract: Objective: This study examined the impact of a financial incentive scheme integrating process and outcome incentives across weight‐loss induction and weight maintenance on 18‐month weight outcomes. Methods: This was a randomized controlled trial. Participants with overweight or obesity ( n = 418; 91% female; 28% racial/ethnic minority) were randomized to an 18‐month, online, group‐based behavioral weight‐control program (Internet‐Only) or the same program with financial incentives provided for 12 months, contingent on self‐regulatory weight‐control behaviors (self‐weighing, dietary self‐monitoring, and physical activity) and weight‐outcome benchmarks (Internet+Incentives). No financial incentives were provided from Months 13 to 18 to examine the durability of weight‐control behaviors and outcomes without incentives. Results: Weight‐loss induction at Month 6 was significantly greater for Internet+Incentives than Internet‐Only (6.8% vs. 4.9%, respectively, p = 0.01). Individuals receiving incentives were significantly more likely to maintain weight loss ≥ 5% at Month 12 (45% in Internet+Incentives vs. 32% in Internet‐Only, p < 0.02) and remain weight stable (39% vs. 27%, respectively, p < 0.01). Internet+Incentives participants also reported significantly greater behavioral engagement through Month 12. However, once incentives ceased, there were no differences in sustained weight outcomes (Month 18), and engagement declined dramatically. Conclusions: Despite promoting greater treatment engagement and initial weight loss, financial incentives as offered in this study did not promote better extended weight control.